Water mobility and microstructure of gluten network during dough mixing using TD NMR. (30th May 2023) - Dufour, Maude; Foucat, Loïc; Hugon, Florence; Dugué, Aurore; Chiron, Hubert; Della Valle, Guy; Kansou, Kamal; Saulnier, Luc
Graphical abstract: Highlights: Water mobility distribution in dough changed with mixing conditions. Four patterns of water distribution were defined as hydration states. Hydration states were discriminated by the most mobile water pools. Changes in hydration states were related to gluten network development. Abstract: This work aimed to establish the relationships between flour components, dough behaviour and changes in water distribution at mixing. TD NMR was used to track water distribution in dough during mixing for different mixing times and hydration levels. Four commercial wheat flours with distinct characteristics were expressly selected to exhibit various dough behaviours at mixing. TD NMR measurements of mixed dough samples revealed four to five water mobility domains depending on the flour type and the mixing modality. A classification tree procedure was used to identify characteristic patterns of water mobility in dough, called hydration states (HS). The HS changes with experimental conditions are highly dependent on flour characteristics, and HS were assigned to physical/chemical changes in the gluten network during dough formation. This study proposes an interpretation of the water distribution in dough based on gluten network development. This will help to adapt the mixing process to the flour characteristics.